MENINGKATKAN MOTIVASI BELAJAR MELALUI PJBL BERBANTUAN TUBE MATERI SISTEM PENCERNAAN MANUSIA SDN PUNTEN 01 - Mar’atun Sholeha; Arina Restian; Ernaz Siswanto (CV. ADIBA AISHA AMIRA, 2026)
Learning is a central aspect in the educational process in an educational institution. This study began with the low interest, enthusiasm, and achievement of students in thematic learning skills in elementary schools, which can affect the quality of education in the school. To achieve the expected results, researchers used the digestive system Tube media for the Natural and Social Sciences (IPAS) subject. Students for low skills felt that the learning method and media were less interesting. The application of the Project Based Learning (PjBL) method in digestive system learning in grade V showed an increase in student learning motivation. This study is a classroom action research (PTK) involving 21 grade V students at SDN Punten 01 Batu. The implementation of actions at the research location was carried out in two cycles. This is evidenced by the increase in the average score. Based on these findings, it can be concluded that the PjBL learning model with Tube media is effective in increasing the motivation and learning outcomes of grade V students in the human digestive system material at SDN Punten 01 Batu.